Peer-Mediated Initial Reading Intervention Strategies for Students with Initial Reading Difficulties - Taboer, Mohammad Arif; Rochyadi, Endang (MIMBAR PGSD Undiksha, 2024)
Initial reading difficulties are a phenomenon that occurs almost every school year in elementary school. In response to this phenomenon, the services developed are remedial learning services. In its implementation, remedial learning services are still a debate. On the one hand, remedial services look more at the effectiveness of activity implementation, but on the other hand still do not answer the holistic needs of students. This research was developed with the aim of developing intervention strategies in serving the reading learning needs of students with reading difficulties without having to serve them in specialized classes. The subjects in this study were two students with initial reading difficulties in the third grade of one of the public schools in East Jakarta. This research method is a mixed method. In the first stage, an assessment of reading difficulties was carried out on students. Furthermore, the required strategy is developed and finally analyzes the effectiveness of the strategy used through visual graphs of the achievement of intervention results. The results of this study suggest that through the intervention strategies developed can provide opportunities to improve students' early reading skills. These results have an implication on the development of educational service models for students with beginning reading difficulties in improving beginning reading skills.